UDP-glucuronic acid availability underlies sex difference in renal expression of nonsulfated Human Natural Killer-1 (HNK-1) glycans - Tomoko Onishi; Hajime Okayama; Hitomi Kitano; Katsuaki Higashi; Naoki Nakagawa; Motohiro Nonaka; Shogo Oka; Jyoji Morise (PLoS ONE, 2025)
Nonsulfated Human Natural Killer-1 (nsHNK-1) glycan is a unique trisaccharide structure terminating in glucuronic acid and synthesized by glucuronyltransferase GlcAT-S. This glycan is specifically expressed in the mouse kidney, particularly in proximal tubules and the thick ascending limb of Henle’s loop. Renal nsHNK-1 glycan exhibits an age-dependent increase, indicating that its expression is strictly regulated. However, previous studies have primarily focused on male kidneys, leaving potential sex differences unexplored. In this study, we found that renal nsHNK-1 glycan expression is significantly higher in female mice compared with male mice. Notably, no sex differences were observed in the expression of N-acetyllactosamine structures, the substrate for glucuronic acid modification, or in GlcAT-S expression levels. Moreover, analysis of knockout mice for GlcAT-P, an isoform of GlcAT-S, confirmed that GlcAT-P also does not contribute to the sex differences in nsHNK-1 glycan expression. These findings prompted us to investigate the intracellular availability of uridine diphosphate glucuronic acid (UDP-GlcA), the donor substrate for GlcAT-S, as a possible contributor to sex-specific renal nsHNK-1 glycan expression. To investigate this hypothesis, we developed a quantitative ELISA to measure intracellular UDP-GlcA levels. In vivo , wild-type female mice exhibited lower renal UDP-GlcA levels compared with males. However, this difference was abolished in GlcAT-S knockout mice, suggesting enhanced UDP-GlcA consumption in female mice. In HK-2 cells, derived from human proximal tubular epithelium, cultivation under high-glucose conditions elevated intracellular UDP-GlcA, resulting in increased nsHNK-1 glycan expression. Conversely, stimulation of UDP-GlcA consumption via glucuronidation using 4-methylumbelliferone suppressed the high-glucose-induced increase in nsHNK-1 glycan expression levels. Taken together, these findings identify UDP-GlcA availability as a key determinant of nsHNK-1 glycan biosynthesis in the kidney, highlighting a novel regulatory mechanism that contributes to sex-specific glycan expression.